2010
DOI: 10.1177/0898264310383156
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Inpatient and Emergency Department Utilization for Ambulatory-Care-Sensitive Conditions: Relationship With Alcohol Consumption

Abstract: Objectives-This study examined the relationship between drinking that exceeds guidelinerecommended limits and acute-care utilization for ambulatory-care-sensitive conditions (ACSCs) by older Medicare beneficiaries.Methods-This secondary data analysis utilized the 2001-2006 Medicare Current Beneficiary Survey (unweighted n=5,570 community dwelling, past-year drinkers, 65 years and older). Selfreported alcohol consumption (categorized as within-guidelines, exceeding monthly but not daily limits, or heavy episodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Factors associated with comorbid alcohol use among older adults, such as low utilization of preventative care and other psychiatric comorbidity, may lower the threshold for admission, leading alcohol comorbid individuals’ lower overall severity to be admitted. Merrick et al (2011) identified a greater likelihood of an emergency department visit for ambulatory care–sensitive conditions among heavy drinking older adults. Similarly, those with alcohol-related diagnoses may be admitted with lower overall depression severity, because alcohol use disorders are associated with increased risk of suicide in older adults (Blow, Brockmann, & Barry, 2004; Conwell, Duberstein, & Caine, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with comorbid alcohol use among older adults, such as low utilization of preventative care and other psychiatric comorbidity, may lower the threshold for admission, leading alcohol comorbid individuals’ lower overall severity to be admitted. Merrick et al (2011) identified a greater likelihood of an emergency department visit for ambulatory care–sensitive conditions among heavy drinking older adults. Similarly, those with alcohol-related diagnoses may be admitted with lower overall depression severity, because alcohol use disorders are associated with increased risk of suicide in older adults (Blow, Brockmann, & Barry, 2004; Conwell, Duberstein, & Caine, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Older‐adult ED visitors with fall‐related injuries often require substantial recurrent health care use; however, drinking problems can interfere with continuing treatment and recovery. In general, older adults with drinking problems have been found to use primary and preventive care less often than their age peers without drinking problems . One study also found that problem drinking was associated with worse self‐perceived health among older‐adult patients in the year following an ED visit …”
Section: Discussionmentioning
confidence: 99%
“…First, data on substance misuse were limited to diagnoses of alcohol and drug use disorders, which tend to be low among older adults. Adverse effects of drinking that do not meet alcohol use disorder diagnostic criteria may be as likely as alcohol use disorders to precipitate ED use among older adults . NEDS should include data on at‐risk and binge/heavy drinking to provide more insight into the effects of alcohol use on presenting problems and outcomes.…”
Section: Limitationsmentioning
confidence: 99%
“…Hearing disability has been shown to compromise well-being among older adults [135], those experiencing late onset deafness showing significantly lower well-being [136]. How older adults manage end-of-life medical decision making has been linked to their personal and affiliative beliefs, rather than to a lack of autonomy [137]. …”
Section: Scientific Advances On Psychological Well-beingmentioning
confidence: 99%